Non- interest income and bank performance in Malaysia: The role of bank size for sustainable growth - Meyappan, Baskaran; Mazlan, Ahmad Rizal; Yusof, Rosylin Mohd (Asian Economic and Financial Review, 2025)
This research examines the effect of non-interest income on banks' performance in Malaysia, focusing on how diversification affects banks of different sizes. The study utilized a balanced panel data set of 14 commercial banks from 2008 to 2023 and employed panel Autoregressive Distributed Lag (ARDL) methodology, using Pooled Mean Group (PMG) to identify how income diversification influences bank performance across various bank sizes in Malaysia. The findings reveal that large banks benefit from non-interest income in both the short and long term, whereas small banks still depend on traditional banking in the long term. The reliance of small banks significantly affects the overall performance of the banking sector in Malaysia. It is recommended that regulators create a supportive framework for smaller banks to diversify into non-interest income activities, especially incorporating fintech, which has driven innovation in the financial industry. The study also highlights the regulator’s role in promoting non-interest-based revenue by encouraging industry players to adopt fintech innovations. This will help improve the stability and performance of Malaysia's overall banking sector, equipping banks to face future challenges.